2005
DOI: 10.1007/s00420-005-0001-7
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to toluene and its possible causative role in renal damage development in shoe workers

Abstract: Our findings support the hypothesis that toluene may be a factor associated with the presence of renal damage in exposed shoe workers. As NAG activity is increased, we believe the lesion initiates in the renal tubular cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…More importantly, the relationship between the degree of contamination at the work sites and possible health risk has not been fully understood yet. In a previous study we found that shoe workers exposed to toluene had levels well above the permissive limits of the Mexican Oficial Norm (González- Yebra et al 2006). Nevertheless, at that time we did not measure any other compounds potentially present in air environments of the factories in Leon city.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…More importantly, the relationship between the degree of contamination at the work sites and possible health risk has not been fully understood yet. In a previous study we found that shoe workers exposed to toluene had levels well above the permissive limits of the Mexican Oficial Norm (González- Yebra et al 2006). Nevertheless, at that time we did not measure any other compounds potentially present in air environments of the factories in Leon city.…”
Section: Discussioncontrasting
confidence: 45%
“…The main industrial activity in the city of Leon, Mexico is related with shoe manufacturing, and the laboral environment of many of these workers is contaminated by a great variety of organic solvents. In our previous study, we found that the urinary toluene levels were above those established by the Mexican Official Norm, however, we did not test other solvents such as acetone, methyl ethyl acetone (MEK) and ethyl acetate (González-Yebra et al 2006). …”
Section: Introductionmentioning
confidence: 84%
“…Several studies have examined the role of organic solvent exposure in a population of patients with glomerulonephritis [17][22]. Some of these studies have demonstrated a significant association between hydrocarbon exposure and the development of glomerulonephritis, and this association has been further confirmed by more studies.…”
Section: Discussionmentioning
confidence: 95%
“…Accordingly, health effects due to occupational solvent exposure are a focus of continuous attention. Whereas the health effects are typically on the central nervous system (Lee et al 1988;Liu et al 1988;Edling 1990;Cai et al 1991;Houck et al 1992;Uchida et al 1993;Ukai et al 1993;Nelson et al 1994;Ihrig et al 2005), effects on the liver (e.g., Fleming et al 1990), the kidneys (e.g., Franchini et al 1983;Ana-Lilia et al 2005;Voss et al 2005) and the peripheral nervous system (Inoue et al 1970;Cianchetti et al 1976;Takeuchi 1993) were also described, and even insidious effects on the reproductive functions (Huel et al 1990) as well as carcinogenicity (Chen and Seaton 1996) other than wellknown benzene-associated leukemia (Aksoy 1985) are suspected. One of the problems in the analysis for causative factors is variety of solvents used in workplaces.…”
Section: Introductionmentioning
confidence: 96%